Teaching in the online classroom : surviving and thriving in the new normal - Lemov, Doug, 1967- (Hoboken, NJ : Jossey-Bass, a Wiley brand, 2020)
"Although the transition to online education is happening more abruptly than anyone anticipated, technology-supported teaching may be here to stay. This guide explores the challenges involved in online teaching and guides educators and administrators to identify and understand best practices. It is a valuable tool to help you and your students succeed in synchronous and asynchronous settings this school year and beyond. Learn strategies for engaging students more fully online. Find new techniques to assess student progress from afar. Discover tools for building online classroom culture, combating online distractions, and more".
Synchronous and asynchronous learning / Hannah Solomon and Beth Verrilli -- Dissolve the screen / Jen Rugani and Kevin Grijalva -- Culture of attention and engagement / Colleen Driggs and Jaime Brillante -- Pause points / Hilary Lewis and Brittany Hargrove -- Accountability loops and checking for understanding / Emily Badillo, Jen Rugani, and Hannah Solomon -- Procedures and routines / Darryl Williams and Dan Cotton -- Classroom tech / Rob Richard and John Costello -- Coda: Planning for the future / Erica Woolway, Emily Badillo, and Doug Lemov.
Includes bibliographical references (p. 178).
Keywords: Web-based instruction; Computer-assisted instruction; Educational technology